2011
DOI: 10.1007/s10875-011-9540-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Th22 Cells Correlated with Th17 Cells in Patients with Rheumatoid Arthritis

Abstract: Together, our results indicated a possible role of Th22 pure Th17 cells and Th17 cells in RA, and blockade of the interleukin-22 may be a reasonable therapeutic strategy for RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 38 publications
12
94
2
5
Order By: Relevance
“…The balance or interplay between various immune cells reflects the reciprocity of anti-and proinflammatory driving forces, which serves as a promising clinical assessment predictor. A positive relationship between circulating Th17 and Th22 frequencies identified in our OSAS children had been demonstrated in various diseases (10)(11)(12).This functional synergism of Th22 and Th17 cells could lead to a dramatic and persistent inflammation in OSAS. On the other hand, Tan et al (13,14) demonstrated that children with OSAS had a lower percentage of Tregs than controls.…”
Section: The Imbalance Of Cd4 + T-lymphocyte Subsetssupporting
confidence: 68%
“…The balance or interplay between various immune cells reflects the reciprocity of anti-and proinflammatory driving forces, which serves as a promising clinical assessment predictor. A positive relationship between circulating Th17 and Th22 frequencies identified in our OSAS children had been demonstrated in various diseases (10)(11)(12).This functional synergism of Th22 and Th17 cells could lead to a dramatic and persistent inflammation in OSAS. On the other hand, Tan et al (13,14) demonstrated that children with OSAS had a lower percentage of Tregs than controls.…”
Section: The Imbalance Of Cd4 + T-lymphocyte Subsetssupporting
confidence: 68%
“…Th22 cells also produced IL-22 and the expression of Th22 cells. IL-22 were significantly elevated in RA patients 5,6 . More importantly, Th17/22 cells showed positive correlations with IL-22, C-reactive protein, and DAS28 data 6 .…”
Section: To the Editormentioning
confidence: 88%
“…Moreover, Th17 cells are clearly associated with the development of pathology in other parasitic infections, including Schistosoma mansoni (24,25), Leishmania major (26,27), and Toxoplasma gondii (28) infections. Similarly, although Th22 cells (which primarily express the prototypical cytokine IL-22) are thought to play an anti-inflammatory role in certain settings (29), they have been implicated in the pathogenesis of a variety of inflammatory diseases, including psoriasis (30), systemic lupus erythematosus (31), and rheumatoid arthritis (32).…”
Section: Discussionmentioning
confidence: 99%